Targeting Resident Memory T Cells for Cancer Immunotherapy - Blanc, Charlotte; Hans, Sophie; Tran, Thi; Granier, Clemence; Saldman, Antonin; Anson, Marie; Oudard, Stephane; Tartour, Eric (Frontiers in Immunology, 2018)
A novel population of memory CD8+ T cells called resident memory T cells (TRM) has been identified based on their phenotype (CD103, CD69) and on their local tissue residency without recirculating in the blood. These cells have been implicated in protective immune response against pathogens in both animal models and humans. Their role in cancer is just emerging as a key player in tumor immunosurveillance. Many properties of these cells suggest that they could control tumor growth: (i) they respond much faster to reexposure to cognate antigen than circulating memory cells, (ii) they express high levels of cytotoxic molecules, and (iii) they are enriched in tumor-specific T cells in close contact with tumor cells. TRM are present in many human cancers and are associated with a good clinical outcome independently of the infiltration of CD8+ T cells. It has been recently shown that the efficacy of cancer vaccines depends on their ability to elicit TRM. In adoptive cell therapy, the transfer of cells with the ability to establish TRM at the tumor site correlates with the potency of this approach. Interestingly, TRM express immune checkpoint molecules and preliminary data showed that they could expand early during anti-PD-1 treatment, and thus be considered as a surrogate marker of response to immunotherapy. Some cues to better expand these cells in vivo and improve the success of cancer immunotherapy include using mucosal routes of immunization, targeting subpopulations of dendritic cells as well as local signal at the mucosal site to recruit them in mucosal tissue.